African Perspective of the Ukrainian Crisis: Assessments and Actions from China - FITUNI Olga Leonidovna (Ученые записки Института Африки Российской академии наук)
The article is devoted to the assessment by the PRC analytical community of the impact of the Ukrainian crisis on the development of African countries, China-Africa relations and relations between Beijing and Western countries. The overall official position of the Chinese authorities regarding the crisis was detailed in a document distributed at the end of February 2023 entitled "China's position on the political settlement of the Ukrainian crisis." The publications of Chinese scientists and analysts concerning the African perspective of the problem, which were published mainly before the advent of the Government paper, dealt almost exclusively with aspects of the influence of the Special Military Operation on the intensification of the food crisis, the disruption of global value chains and the debt problem. They dealt with a fairly wide range of technical issues, but in the overwhelming majority they did not reveal the deep foundations and initial prerequisites for the problems that had arisen. At the same time they closely resonated with Western objectivist approaches to these issues.